Prevalence of Endophthalmitis after Intravitreal Injection of Avastin (Bevacizumab) in Patients Wearing Masks - A Najafi; F Jafarzade; H Ojaghi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Although the likelihood of endophthalmitis after intravitreal injection is low, one of the side effects of this injection is blindness. With the prevalence of the COVID-19 pandemic and the necessity of mask use in patients and physicians, mask use has increased. Previous studies have reported a high risk of endophthalmitis after intravitreal injection in patients who wore masks. The present study was conducted to investigate the pattern of endophthalmitis after intravitreal injection of Avastin (Bevacizumab) in patients wearing masks. Methods: This prospective cohort study was conducted on 3938 patients who underwent intravitreal injection from March 2021 to March 2022 at the eye surgery center. Bevacizumab injection was performed after local anesthesia in the operating room and under sterile conditions. Local antibiotic drops (chloramphenicol) were then used. It should be noted that patients' masks were not removed at any of the stages mentioned. Patients were followed up one week after discharge to be examined for infection. Findings: A total of 3938 patients were included in the study, 56.6% of whom were male and 43.4% were female. The mean age of the patients was 39.61±16.10 years. Moreover, no significant difference was observed between men and women. The highest frequency of injection was related to diabetic macular edema (27.8%) and the lowest frequency was related to neovascular glaucoma (0.5%). Only one patient was diagnosed with endophthalmitis after intravitreal injection. In addition, no significant relationship was found between age, gender, and the occurrence of endophthalmitis. Conclusion: According to the results of this study, the incidence of endophthalmitis after intravitreal injection is very low, and the use of a face mask in patients has no effect on the occurrence of endophthalmitis.